2004
DOI: 10.1021/jp049227x
|View full text |Cite
|
Sign up to set email alerts
|

A Periodic Density Functional Theory Study of Cumene Formation Catalyzed by H-Mordenite

Abstract: A periodic density functional theory study of the alkylation of benzene with propene in proton-exchanged mordenite has been achieved. The two different reaction routes that are usually proposed for this reaction, namely the direct and the step-by-step reaction pathways, have been investigated. The explicit consideration of the zeolite catalyst framework allows a better level of description of the interactions between the catalyst framework and the reaction than what is obtained with the cluster approach method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
1

Year Published

2008
2008
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 63 publications
(180 reference statements)
1
40
1
Order By: Relevance
“…2 Structure VIII again shows the bifunctional role of the zeolite acid sites, and the participation of oxygen atoms that are not bonded to the alkoxide intermediate. Other C-C bond forming reactions (such as ethylene dimerization to form n-butenes) proceed in a similar fashion (Namuangruk et al, 2005).…”
Section: Classical Brønsted Acid Catalysismentioning
confidence: 98%
See 4 more Smart Citations
“…2 Structure VIII again shows the bifunctional role of the zeolite acid sites, and the participation of oxygen atoms that are not bonded to the alkoxide intermediate. Other C-C bond forming reactions (such as ethylene dimerization to form n-butenes) proceed in a similar fashion (Namuangruk et al, 2005).…”
Section: Classical Brønsted Acid Catalysismentioning
confidence: 98%
“…Both alkoxide (IV), and carbenium ion (V) intermediates are highly reactive, and can form new carbon-carbon bonds with organic molecules physisorbed inside the zeolite pores. An important industrial reaction conducted over zeolites is the synthesis of cumene from propene and benzene (Rozanska et al, 2005). 2 It has been reported that the kinetically relevant pathway for the formation of cumene is a sequential reaction in which propene reacts with a Brønsted acid site to form an isopropoxide intermediate.…”
Section: Classical Brønsted Acid Catalysismentioning
confidence: 99%
See 3 more Smart Citations